2014
DOI: 10.1007/s10661-014-4190-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metals contamination in Mamut river sediments using sediment quality guidelines and geochemical indices

Abstract: This paper describes the concentration of selected heavy metals (Co, Cu, Ni, Pb, and Zn) in the Mamut river sediments and evaluate the degree of contamination of the river polluted by a disused copper mine. Based on the analytical results, copper showed the highest concentration in most of the river samples. A comparison with Interim Canadian Sediment Quality Guidelines (ICSQG) and Germany Sediment Quality Guidelines (GSQG) indicated that the sediment samples in all the sampling stations, except Mamut river co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…On the other hand, Cd amount in this manuscript was lower than those detected in the Fusaro Lagoon by Arienzo et al [68], in the Sardinia Coast by Schintu et al [69] and in the Calore River by Zuzolo et al [25] in Italy, in the Heer River (China) by Zhu et al [70] and Xiangjiang River (China) by Li et al [64]. Excluding Palma de Mallorca Bay (Spain) by Moukhchan et al [71], Northern Tyrrenian Sea (Italy) by Piazzolla et al [72] and the Karstic River (China) by Ling et al [63], at all each sampling point, Ni concentration found in the sediments of Volturno River was lower compared to data reported in previous studies (Table 5) [3,25,35,64,70,73]. The concentrations of Cr, Cu, Pb and Zn found in the sediments of this river were lower than literature data (Table 5).…”
Section: Resultsmentioning
confidence: 87%
“…On the other hand, Cd amount in this manuscript was lower than those detected in the Fusaro Lagoon by Arienzo et al [68], in the Sardinia Coast by Schintu et al [69] and in the Calore River by Zuzolo et al [25] in Italy, in the Heer River (China) by Zhu et al [70] and Xiangjiang River (China) by Li et al [64]. Excluding Palma de Mallorca Bay (Spain) by Moukhchan et al [71], Northern Tyrrenian Sea (Italy) by Piazzolla et al [72] and the Karstic River (China) by Ling et al [63], at all each sampling point, Ni concentration found in the sediments of Volturno River was lower compared to data reported in previous studies (Table 5) [3,25,35,64,70,73]. The concentrations of Cr, Cu, Pb and Zn found in the sediments of this river were lower than literature data (Table 5).…”
Section: Resultsmentioning
confidence: 87%
“…Pollution indices are an efficient and rapid tool for producing a single value, the indicator, emanating from different parameters. Most of the indices have been employed globally to study the contamination of toxic heavy metals in river sediments [17,18]. Pollution indices are powerful tools for evaluating, developing, and conveying raw environmental data into more meaningful information for politicians and decision-makers [19].…”
Section: Introductionmentioning
confidence: 99%
“…Measured EF value ranges of 2.80–4.754, 0.823–1.491, 0.795–1.446, 1.646–4.957, 0.995–3.262 for Cr, Cu, Zn, As and Pb among the sites, respectively ( Table 4 ). According to Mohammad et al [ 51 ], when EF < 1.5, the elements are most likely earth’s cluster origin, resulting from natural processes. In this study, Fe showed enrichment factor 1 for all the sites, indicating cluster metal, coming from weathering practice [ 52 ].…”
Section: Resultsmentioning
confidence: 99%